Structural support in Algeria: Does it affect the Entrepreneurial intention of university students - BOUCIF, Sidahmed; TOUAITI, Mustapha (Journal of Finance & Corporate Governance, 2017)
This study aims to determine the impact of the structural support on the entrepreneurial intention among university students this is based on the theory of planned behavior; the study was conducted using structural equations modeling on a sample of final year business students at the University of Annaba. Firstly, the results showed that the students have a good attitude about the entrepreneurial and they realize that they are able to control their behavior, these factors impact more positively on their entrepreneurial intention. Finally, with regard to the effect of structural support has been found to have a weak effect on students' attitude and we did not find any impact of this factor on perceived behavior control and there entrepreneurial intention.